“We were victims of our families’ uncooperative behavior”: Problems Faced by School Dropouts in Rural Ghana - Cecilia Sem Obeng (Nordic Journal of African Studies, 2006)
Using the narratives by school dropouts, their parents, and teachers, this paper discusses the causes and consequences of dropping out of school. The paper demonstrates that some rural children in Ghana do not attend school due to cultural conventions on politeness, divorce, male privileges, poverty, the domestic role and economically viable ventures performed by children (with participation in such chores often overshadowing care and support for them), and weak teacher-student support system which prevents teachers from recognizing the factors hampering the children’s education. To rectify this precarious situation, the paper calls on educators, policy makers, the Social Welfare Department, parents and students to work in concert with each other.